2013
DOI: 10.2320/matertrans.m2012352
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ARB Processing on Fatigue Crack Closure in Commercially Pure Titanium

Abstract: Fatigue crack closure in commercially pure titanium sheets severely deformed using the accumulative roll-bonding (ARB) process were investigated. Sheet processed through 6 cycles of ARB consists of fine equiaxed grains and elongated lamellar grains and shows a high 0.2% proof stress of 790 MPa. Fatigue crack closure was not observed in the ARB processed sheet. The effective threshold stress intensity factor ranges, "K th.eff , of the ARB processed sheets and starting sheet are nearly the same. On the other han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…However, the RSA450 sample exhibits a large fatigue ratio (0.56) at a high tensile strength of 870 MPa. One can see that the HCF behavior of the RSA450 sample differs significantly from that of conventional CG and UFG CP-Ti [22,23,24,25,26,27,28,29,30,31,32,33,34,35,39], and is close to that of the Ti-6Al-4V alloy.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…However, the RSA450 sample exhibits a large fatigue ratio (0.56) at a high tensile strength of 870 MPa. One can see that the HCF behavior of the RSA450 sample differs significantly from that of conventional CG and UFG CP-Ti [22,23,24,25,26,27,28,29,30,31,32,33,34,35,39], and is close to that of the Ti-6Al-4V alloy.…”
Section: Resultsmentioning
confidence: 84%
“…The highest HCF limit of 460 MPa was reported in UFG CP-Ti (grade 2), produced by ECAP [22,23,24]. It was observed that the fatigue crack initiation was significantly delayed in the transverse direction due to the strong crystallographic texture of UFG Ti fabricated by accumulative roll bonding (ARB), while the crack propagation behavior was not obviously affected [25,26,27]. Although these studies revealed some interesting fatigue behaviors of UFG CP-Ti, investigations into the fatigue properties of UFG CP-Ti are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of ultra-fine grained materials produced by ECAP [1], HPT [2], ARB [3], Warm tempforming [4], HCR [5], etc., are actively being advanced. An austenitic stainless steel, which has a grain size less than 2 µm, has been commercialized since 2013 [6].…”
Section: Introductionmentioning
confidence: 99%
“…The studies of ultra-fine grained materials produced by ECAP [1], HPT [2], ARB [3], Warm tempforming [4], HCR [5], etc., are actively being advanced. An austenitic stainless steel, which has a grain size less than 2 µm, has been commercialized since 2013 [6].…”
Section: Introductionmentioning
confidence: 99%